Multidrug-Resistant Klebsiella pneumoniae Complex From Clinical Dogs and Cats in China: Molecular Characteristics, Phylogroups, and Hypervirulence-Associated Determinants - Zhang, Zhenbiao; Zhang, Liu; Dai, Hegen; Zhang, Haixia; Song, Yu; An, Qi; Wang, Jianzhong; Xia, Zhaofei (Frontiers in Veterinary Science, 2022)
Klebsiella pneumoniae complex is an increasingly important bacterial pathogen that is capable of causing severe organs and life-threatening disease. This study aimed to investigate the multidrug resistance, phylogroups, molecular characterization, and hypervirulence-associated determinants of the complex, which were isolated from clinical diseased dogs and cats. A total of 35 K. pneumoniae complex (2.3%; 95% confidence interval, 1.6–3.2) isolates were identified from 1,500 samples, all of which were collected randomly from veterinary hospitals in the 12 regions across China. Antimicrobial susceptibility testing showed that isolates were extremely resistant to amoxicillin–clavulanate (82.9%) and trimethoprim–sulfamethoxazole (77.1%). The rate of multidrug-resistant reached an astonishing 82.9% and found a carbapenemase-producing strain carrying IncX3-blaNDM−5 derived a cat from Zhejiang. The prevalence rates of extended-spectrum β-lactamase gene blaCTX−M and plasmid-mediated quinolone resistance gene aac(6')Ib-cr were 51.4% and 45.7%, respectively. The resistance gene aph(3')-Ia of isolates from cats was more significantly (p < 0.05) prevalent than that from dogs. Likewise, K. pneumoniae complex harbored hypervirulence-associated genes ybt (11.4%), iuc (5.7%), and iroB (2.9%). Three (8.6%) of the 35 isolates were determined as hypermucoviscous by the string test. Lipopolysaccharide serotype O1v2 had the highest percentage of 25.7%, but capsular serotypes presented diversity distribution among the isolates. The core–genome phylogenetic tree demonstrated most of the isolates belonged to the KpI phylogroup (91.4%). Multilocus sequence typing analysis identified 25 different STs; ST15 and ST37 were the most abundant accounting for isolates, followed by ST307, ST656, ST1408, and ST4566. In addition, the prevalence of IncFIB-type plasmid for cat isolates was significantly higher (p < 0.05) than that for dogs. Sequences of IncX3 in blaNDM−5-positive strain contained regions showing >99% nucleotide sequence identity to the reference plasmid pNDM-MGR194 from the human.